Winding type battery cell and battery

By adopting a double-layer coating structure and setting a recessed area in the positive electrode of the battery, the problems of fast electrolyte consumption and poor safety of lithium cobalt oxide-ternary material system batteries under high voltage are solved, and the cycle stability of the battery is improved. Safety performance.

CN119208762APending Publication Date: 2024-12-27ZHUHAI COSMX BATTERY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411397258.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Lithium cobalt oxide-ternary material system battery has safety and circulation problems under high voltage. The rapid attenuation of ternary materials leads to accelerated electrolyte consumption, which is prone to electrolyte bridge breakage and black spot lithium, affecting the cycle life and safety of the battery. sex.

Method used

The positive electrode sheet adopts a double-layer coating structure, the ternary material and lithium cobalt oxide material are respectively arranged in different active layers, and a recess is provided in the bending area of ​​the winding battery cell to improve the wetting property of the electrolyte and the positive electrode sheet. uniformity, reduce mechanical strength and prolong cycle life.

Benefits of technology

It improves the safety performance and cycle stability of the battery, extends the service life of the battery, reduces the risk of black spot lithium caused by electrolyte bridge breakage, and enhances the rate performance and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208762A_ABST
    Figure CN119208762A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a winding type battery cell and a battery. The positive plate comprises a positive current collector and a positive active material layer located on the surface of one side or two sides of the positive current collector, the positive active material layer comprises a first positive active layer and a second positive active layer, the first positive active layer is located on the surface of the positive current collector, and the second positive active layer is located on the surface of the second positive current collector. The second positive electrode active layer is located on the surface of the first positive electrode active layer, the first positive electrode active layer comprises a ternary material, the second positive electrode active layer comprises a lithium cobalt oxide material, the positive plate comprises a concave part area, the concave part area corresponds to a bending area of the winding type battery cell, the concave part area comprises a concave part, and the concave part corresponds to the bending area of the winding type battery cell. The positive plate simultaneously meets the following relational expressions: h is more than or equal to 0.01 H and less than or equal to 0.5 H-0. 01; h = h1 + h2; 40 < = h1 + h2 * D2 / D1 < = 400. The battery disclosed by the invention is high in cycling stability, long in service life, high in safety performance and low in expansion rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a wound battery cell and a battery comprising the wound battery cell. Background Art

[0002] Lithium-ion batteries have the advantages of high platform voltage, long cycle life, high energy density, and no memory effect, and are widely used in mobile phones, laptops, smart wearables, power tools, etc. Lithium cobalt oxide is usually used as the positive electrode active material, but the metal cobalt resources are relatively scarce and the cost is also high, which to a certain extent limits its industrial application.

[0003] The different design ratios of nickel, cobalt and manganese in ternary materials can balance the overall cost of the materials and achieve different performance priorities. However, compared with lithium cobalt oxide, ternary materials have poor high voltage resistance, more intense side reactions with electrolytes under high voltages, faster electrolyte consumption during battery cycles, and are more prone to safety and cycle problems such as electrolyte breakage. Summary of the invention

[0004] In order to ensure that the energy density of the positive electrode meets the use requirements while reducing costs, the current method is to mix some low-cost ternary materials into the lithium cobalt oxide material. However, due to the large particles of lithium cobalt oxide and the small particles of ternary materials, it is difficult to achieve complete uniformity of ternary materials and lithium cobalt oxide materials by mechanically mixing ternary materials and lithium cobalt oxide materials, and the capacity of ternary materials is higher than that of lithium cobalt oxide materials, but the decay of ternary materials is faster than that of lithium cobalt oxide materials under high voltage. From a local point of view, the area enriched with ternary materials needs to absorb more lithium ions due to its higher capacity in the initial stage of the cycle, but the negative electrode is uniform as a whole, and the concentration difference caused by the transmission of lithium ions to the ternary materials is getting larger and larger, which will cause greater polarization of the negative electrode sheet; in the later stage of the cycle, the decay of ternary materials is accelerated, resulting in the poor ability of the area enriched with ternary materials to absorb lithium ions, and the corresponding negative electrode area can receive fewer lithium ions, so the area enriched with ternary materials is prone to black spots or lithium precipitation. Therefore, how to ensure that lithium cobalt oxide-ternary material system batteries have higher safety and lower cost without affecting the electrochemical performance of the battery is a technical problem that needs to be solved urgently.

[0005] In addition, research has found that the lithium cobalt oxide-ternary material system consumes electrolyte quickly, and in order to pursue higher capacity and higher energy density of the battery, it is inevitable to increase the compaction density of the electrode and the surface density of the coating, which makes it more likely that black spots and lithium precipitation will appear at the arc of the battery cell due to electrolyte bridge breakage, ultimately leading to failure of the lithium cobalt oxide-ternary material system battery.

[0006] In order to solve the above technical problems, the present invention provides a wound cell and a battery including the wound cell. The positive electrode sheet of the present invention adopts a double-layer coating method to improve the uniformity of lithium cobalt oxide material and ternary material per unit area, improve the situation that black spots or lithium deposition are easy to appear on the positive electrode sheet, and set a concave portion in the bending area of ​​the corresponding wound cell, which can improve the wettability of the electrolyte to the positive electrode sheet and reduce the risk of lithium deposition in the bending area, thereby solving the problem of black spot lithium deposition caused by electrolyte bridge breakage. At the same time, the setting of the concave portion reduces the mechanical strength, correspondingly improves its elasticity, reduces the expansion rate of the bending area, improves the cycle performance of the battery, and extends the cycle life of the battery.

[0007] A first aspect of the present invention provides a wound battery cell, wherein the wound battery cell comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, the positive electrode active material layer comprises a first positive electrode active layer and a second positive electrode active layer, the first positive electrode active layer is located on the surface of the positive electrode current collector, the second positive electrode active layer is located on the surface of the first positive electrode active layer, the first positive electrode active layer comprises a ternary material, the second positive electrode active layer comprises a lithium cobalt oxide material, the positive electrode sheet comprises a concave area, the concave area corresponds to the bending area of ​​the wound battery cell, the concave area comprises a concave portion, and the positive electrode sheet satisfies the following relationship at the same time: 0.01H≤h≤0.5H-0.01; H=h1+h2; 40≤h1+h2*D2 / D1≤400;

[0008] Among them, the thickness of the positive electrode active material layer is H, in μm, the depth of the recess is h, in μm, the thickness of the first positive electrode active layer is h1, in μm, the thickness of the second positive electrode active layer is h2, in μm, the average particle size of the ternary material is D1, in μm, and the average particle size of the lithium cobalt oxide material is D2, in μm.

[0009] A second aspect of the present invention provides a battery, which includes the wound battery cell described in the first aspect of the present invention.

[0010] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0011] (1) The positive electrode adopts a double-layer positive electrode active layer structure, which can improve the uniformity of lithium cobalt oxide material and ternary material per unit area, thereby reducing the problem of local black spots or lithium precipitation at the positive electrode interface caused by mechanical mixing and coating, and the first positive electrode active layer including the ternary material is arranged on the side close to the surface of the positive electrode collector, and the second positive electrode active layer including the lithium cobalt oxide material is arranged on the side away from the positive electrode collector, wherein the thermal runaway temperature of the ternary material is low, and the thermal runaway temperature of the lithium cobalt oxide material is high. This structure can match the direction of temperature transfer from the outside to the inside of the positive electrode sheet. When the ternary material located on the inside reaches the failure temperature, the lithium cobalt oxide material located on the outside has not yet failed. At this time, the heat dissipated by the failure of the ternary material can be delayed to cause the internal temperature of the battery to rise, thereby improving the safety performance of the battery. In addition, the specific surface area of ​​lithium cobalt oxide is small, and arranging it on the surface can reduce the consumption of electrolyte by the positive electrode sheet, thereby improving the situation where black spots and lithium precipitation appear on the main interface of the battery cell due to electrolyte bridge rupture;

[0012] (2) By providing a concave portion in the bending area of ​​the corresponding wound battery cell, the pore structure of the positive electrode sheet can be improved, the wettability of the electrolyte to the positive electrode sheet can be improved, and the electrolyte retention capacity of the positive electrode sheet can be improved during a long cycle, thereby solving the problem of black spot lithium precipitation caused by electrolyte bridge breakage, thereby improving the battery rate and cycle stability performance;

[0013] (3) By controlling the relationship between the average particle size of the ternary material, the average diameter of the lithium cobalt oxide material, the thickness of the positive electrode active material layer, the thickness of the first positive electrode active layer, the thickness of the second positive electrode active layer and the depth of the recess, on the one hand, the consumption rate of the electrolyte on the positive electrode side can be slowed down, so that the depth of the recess does not need to be too deep, thereby solving the problem of lithium precipitation in the bending zone without causing excessive loss of the active material on the positive electrode side; on the other hand, the positive electrode sheet can be further optimized, thereby reducing the cost while maintaining high safety performance and cycle stability.

[0014] Other features and advantages of the present invention will be described in detail in the following detailed description.

[0015] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 FIG. 1 is a schematic structural diagram of a positive electrode sheet according to an embodiment of the present invention.

[0017] Figure 2 FIG. 1 is a schematic diagram of a concave portion in a positive electrode sheet according to an embodiment of the present invention.

[0018] Figure 3 It is a schematic diagram showing that holes are distributed in a matrix in one embodiment of the present invention.

[0019] Figure 4 FIG. 1 is a schematic diagram showing a matrix distribution of slots in one embodiment of the present invention.

[0020] Figure 5 FIG. 1 is a schematic diagram showing a groove penetrating both side edges of a positive electrode sheet in a width direction in an embodiment of the present invention.

[0021] Figure 6 The figure shows a schematic diagram of an embodiment of the invention in which the groove does not penetrate the two side edges of the positive electrode sheet in the width direction.

[0022] Figure 7 FIG. 1 is a schematic diagram showing the width of a groove in an embodiment of the present invention.

[0023] Figure 8 FIG. 2 is a second schematic diagram showing the width of the groove in one embodiment of the present invention.

[0024] Fig. 9 FIG. 1 is a schematic diagram of the structure of the adhesive tape in one embodiment of the present invention.

[0025] Fig.10 FIG. 1 is a SEM image of a positive electrode sheet in one embodiment of the present invention, wherein: Fig.10 (a) is a 100 μm SEM image with the weight content of the ternary material and the lithium cobalt oxide material as the basis, and the ratio of the weight content of the ternary material to the weight content of the lithium cobalt oxide material is 20%:80%; Fig.10 (b) Fig.10 (a) SEM image magnified to 20 μm; Fig.10 (c) is a 100 μm SEM image with a weight content ratio of the ternary material to the lithium cobalt oxide material of 40%:60%, based on the sum of the weights of the ternary material and the lithium cobalt oxide material; Fig.10 (d) Fig.10 (c) SEM image magnified to 20 μm.

[0026] Fig.11 It is a schematic diagram showing that the groove occupies the entire recess in one embodiment of the present invention. DETAILED DESCRIPTION

[0027] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints.

[0028] It should be noted that the numerical expressions such as "first" and "second" in the present disclosure are only used to distinguish different substances or usage methods, and do not represent the difference in order.

[0029] A first aspect of the present invention provides a wound battery cell, wherein the wound battery cell comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, the positive electrode active material layer comprises a first positive electrode active layer and a second positive electrode active layer, the first positive electrode active layer is located on the surface of the positive electrode current collector, the second positive electrode active layer is located on the surface of the first positive electrode active layer, the first positive electrode active layer comprises a ternary material, the second positive electrode active layer comprises a lithium cobalt oxide material, the positive electrode sheet comprises a concave area, the concave area corresponds to the bending area of ​​the wound battery cell, the concave area comprises a concave portion, and the positive electrode sheet satisfies the following relationship at the same time: 0.01H≤h≤0.5H-0.01; H=h1+h2; 40≤h1+h2*D2 / D1≤400;

[0030] Among them, the thickness of the positive electrode active material layer is H, in μm, the depth of the recess is h, in μm, the thickness of the first positive electrode active layer is h1, in μm, the thickness of the second positive electrode active layer is h2, in μm, the average particle size of the ternary material is D1, in μm, and the average particle size of the lithium cobalt oxide material is D2, in μm.

[0031] like Figure 1 As shown, the positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active material layer 12, the positive electrode active material layer 12 includes a first positive electrode active layer 121 and a second positive electrode active layer 122, the first positive electrode active layer 121 is located on both sides of the positive electrode current collector 1, the second positive electrode active layer 122 is located on the surface of the first positive electrode active layer 121, the first positive electrode active layer 121 includes a ternary material, and the second positive electrode active layer 122 includes a lithium cobalt oxide material, wherein the thickness of the positive electrode active material layer 12 is H, in μm, the thickness of the first positive electrode active layer 121 is h1, in μm, and the thickness of the second positive electrode active layer 122 is h2, in μm. Wherein, the thickness is the length along the thickness direction a.

[0032] The positive electrode sheet may include a recessed area, and the recessed area corresponds to a bending area of ​​the wound battery cell. Figure 2As shown, the positive electrode sheet 1 includes a recessed area 13, and in the positive electrode sheet 1, the recessed area 13 is periodically arranged along the length direction b of the positive electrode sheet. It can be understood that in the positive electrode sheet, the number of recessed areas N is less than the number of bending areas of the wound battery cell, where N is a positive integer, for example, N is 1, 3, 5, 7, 10, 13, 15, 17, 20, 25, 30, 35, 40, 45, 50, 55, 60, 70, 80, 90 or 100.

[0033] The depth of the recess is h, wherein the depth of the recess is the vertical length along the thickness direction a.

[0034] The positive electrode sheet can simultaneously satisfy the following relationships: 0.01H≤h≤0.5H-0.01; H=h1+h2; 40≤h1+h2*D2 / D1≤400 (for example, 40, 50, 80, 100, 120, 150, 180, 200, 220, 250, 300, 350 or 400).

[0035] The positive electrode sheet of the present invention arranges the first positive electrode active layer including the ternary material on the side close to the current collector surface (inner side), and the second positive electrode active layer including the lithium cobalt oxide material on the side away from the positive electrode current collector (outer side). On the one hand, the uniformity of the distribution of the lithium cobalt oxide and the ternary material per unit area is improved, thereby improving the problem of black spots or lithium precipitation at the positive electrode interface caused by mechanical mixing; on the other hand, the ternary material with a lower thermal runaway temperature is arranged on the inner side, and the lithium cobalt oxide material with higher stability is arranged on the outer side, which can ensure that when the ternary material on the inner side fails, the lithium cobalt oxide material on the outer side has not failed, thereby delaying the transfer of heat dissipated due to the failure of the ternary material, thereby improving the safety performance of the battery; on the other hand , the ternary material with a larger specific surface area is arranged in the inner layer, and the lithium cobalt oxide material with a smaller specific surface area is arranged on the outer layer, which can reduce the side reaction between the positive electrode side and the electrolyte, improve the cycle stability of the battery, and can also slow down the consumption rate of the electrolyte on the positive electrode side, thereby extending the service life of the battery. At the same time, the recessed area is cooperatively arranged at the bending area of ​​the positive electrode sheet corresponding to the wound battery cell. The setting of the recessed area can increase the infiltration effect and speed of the electrolyte in the bending area on the positive electrode sheet, increase the liquid storage space of the positive electrode sheet, and increase the liquid storage capacity of the positive electrode sheet, effectively solving the problem of insufficient electrolyte in the late cycle caused by the fast consumption rate of the electrolyte on the positive electrode side, thereby further improving the cycle stability of the battery and extending the service life of the battery. The setting of the recessed area can also increase the CB value at the recessed area of ​​the positive electrode sheet, thereby effectively reducing the risk of lithium precipitation, reducing the mechanical strength of the recessed area, and improving the elasticity of the recessed area, thereby reducing the expansion rate of the bending area. In addition, the positive electrode sheet is controlled to satisfy the following relationship: 0.01H≤h≤0.5H-0.01; H=h1+h2; 40≤h1+h2*D2 / D1≤400, so that the particle size of the lithium cobalt oxide material can be controlled within an appropriate range, while reducing the consumption rate of the electrolyte on the positive electrode side, ensuring that the depth of the recess is also within a relatively appropriate range, and can solve the problem of lithium deposition in the bending zone without causing excessive loss of the positive electrode active material. The problem of lithium deposition in the bending zone will not be significantly improved due to the depth of the recess being too shallow, and the positive electrode active material will not be excessively lost due to the depth of the recess being too deep.

[0036] When h is less than 0.01H, the modification effect on the wetting and long cycle performance of the battery is not obvious; when h is greater than 0.5H-0.01, the loss of positive electrode active materials is large, and at the same time, the consumption of ether nitrile compounds in the electrolyte increases, which reduces the long cycle rate performance and safety performance of the battery.

[0037] When h1+h2*D2 / D1>400, the transmission distance of lithium ions increases and the impedance increases; when h1+h2*D2 / D1<40, the particle sizes of lithium cobalt oxide material and ternary material are quite different and the particle size uniformity is poor, which affects the liquid phase transfer of the electrode, increases the transfer impedance of the interfacial charge, is not conducive to the diffusion of lithium ions in the solid phase, and increases the consumption of electrolyte on the negative electrode side, reducing the kinetic performance of the battery. In addition, agglomeration will occur when preparing the slurry of the first active material layer and the second active material layer, affecting the processing of the electrode.

[0038] In the present invention, by adopting a double-layer coating method and setting a concave area, and controlling the relationship between the average particle size of the lithium cobalt oxide material and the ternary material and the thickness of each active layer, the safety performance and cycle stability of the battery can be improved, the service life of the battery can be extended, and the expansion rate of the battery bending area can be reduced compared with the prior art. In order to further improve the effect, one or more of the technical features can be further optimized.

[0039] In one example, h≤h2, that is, the depth of the concave portion h≤the thickness of the second positive electrode active material layer h2. At this time, the ternary material in the first positive electrode active material located on the surface of the positive electrode current collector will not be exposed, and the thermal stability of the ternary material is poor. Controlling h≤h2 can reduce the risk of exposure of the ternary material, so that the lithium cobalt oxide material forms a protection for the ternary material, and improves the safety of the lithium ion battery. When h>h2, the ternary material with poor stability is easily exposed to cause thermal runaway problems, thereby reducing the safety performance of the lithium ion battery.

[0040] In one example, 3 μm≤h1≤200 μm (eg, 3 μm, 10 μm, 20 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, or 200 μm).

[0041] In one example, 20 μm≤h1≤100 μm.

[0042] In one example, 20 μm≤h2≤200 μm (eg, 20 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, or 200 μm).

[0043] In one example, 50 μm≤h2≤100 μm.

[0044] The thickness h1 of the first positive electrode active layer and the thickness h2 of the second positive electrode active layer may be the same or different.

[0045] In one example, the thickness h1 of the first positive electrode active layer is the same as the thickness h2 of the second positive electrode active layer. It can be understood that the thickness h1 of the first positive electrode active layer is the same as the thickness h2 of the second positive electrode active layer, which means that the value of h1 and the value of h2 can be completely the same, or the difference between the value of h1 and the value of h2 is within ±3 μm.

[0046] When the thickness h1 of the first positive electrode active layer is the same as the thickness h2 of the second positive electrode active layer, the battery can have the advantages of high safety performance, high cycle stability and low cost.

[0047] In one example, the thickness h1 of the first positive electrode active layer is less than the thickness h2 of the second positive electrode active layer. In this case, the battery has higher safety performance and higher cycle stability.

[0048] In one example, the thickness h1 of the first positive electrode active layer is greater than the thickness h2 of the second positive electrode active layer. In this case, the cost of the battery is relatively low.

[0049] In one example, 0<H≤300μm (eg, 20μm, 40μm, 50μm, 80μm, 100μm, 120μm, 150μm, 180μm, 200μm, 220μm, 250μm, 280μm, or 300μm).

[0050] In one example, 100 μm ≤ H ≤ 200 μm.

[0051] In one example, 3 μm ≤ D1 ≤ 15 μm (eg, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm or 15 μm). Controlling the average particle size of the ternary material within the above range can enable the ternary material to have a higher energy density and a higher rate performance.

[0052] In one example, 8 μm ≤ D2 ≤ 25 μm (eg, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm or 25 μm). Controlling the average particle size of the lithium cobalt oxide material within the above range can make the lithium cobalt oxide material have higher safety performance and higher long cycle performance.

[0053] In one example, 10 μm ≤ D2 ≤ 20 μm.

[0054] In the present invention, the average particle size can be obtained by electron microscopy testing, as follows: select 5 active material layers with an area of ​​1 mm×1 mm in the electron microscopy image of the positive electrode sheet, measure the particle sizes of the ternary material and the lithium cobalt oxide material in the area, and take the average value, which is recorded as the average particle size.

[0055] In one example, the median particle size Dv501 of the ternary material is 5 μm-15 μm.

[0056] In one example, the median particle size Dv502 of the lithium cobalt oxide material is 10 μm-20 μm.

[0057] In the present invention, the median particle size can be obtained by testing with a laser particle size analyzer.

[0058] In one example, the specific surface area of ​​the ternary material is greater than the specific surface area of ​​the lithium cobalt oxide material.

[0059] In one example, 20 μm≤h1≤100 μm, and 50 μm≤h2≤100 μm, and 100 μm≤H≤200 μm, and 3 μm≤D1≤15 μm, and 10 μm≤D2≤20 μm, and the specific surface area of ​​the ternary material is greater than the specific surface area of ​​the lithium cobalt oxide material.

[0060] In one example, the specific surface area of ​​the ternary material is 0.3 m 2 / g-1m 2 / g (for example, 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g or 1m 2 / g).

[0061] In one example, the specific surface area of ​​the lithium cobalt oxide material is 0.07 m 2 / g-0.32m 2 / g (for example, 0.07m 2 / g, 0.1m 2 / g, 0.12m 2 / g, 0.15m 2 / g, 0.18m 2 / g, 0.2m 2 / g, 0.22m 2 / g, 0.25m 2 / g, 0.28m 2 / g, 0.3m 2 / g or 0.32m 2 By controlling the specific surface area of ​​the lithium cobalt oxide material within the above range, the side reaction between the lithium cobalt oxide material and the electrolyte can be reduced.

[0062] In one example, the specific surface area of ​​the ternary material is 0.3 m 2 / g-1m 2 / g, and the specific surface area of ​​the lithium cobalt oxide material is 0.07m 2 / g-0.32m 2 / g, and the specific surface area of ​​the ternary material is greater than the specific surface area of ​​the lithium cobalt oxide material.

[0063] In one example, the crystal structure of the lithium cobalt oxide material includes a single crystal.

[0064] In one example, the crystal structure of the lithium cobalt oxide material is a single crystal. When the crystal structure of the lithium cobalt oxide material is a single crystal, the compaction density of the positive electrode sheet is large, the high-voltage performance of the battery is excellent, and the risk of battery gas generation is low.

[0065] In one example, the lithium cobalt oxide material includes a chemical formula of LiCoM x O2 particles, wherein 0≤x≤1, and M includes one or more of Al, Mg, Ti, Zr, V and Mn. The M element may exist in the lithium cobalt oxide material in the form of doping or coating. When the lithium cobalt oxide material includes the M element, the stability of the lithium cobalt oxide material can be further improved.

[0066] In one example, based on the total weight of the lithium cobalt oxide material, the weight content of the M element is 100ppm-20000ppm (for example, 100ppm, 500ppm, 1000ppm, 3000ppm, 5000ppm, 8000ppm, 10000ppm, 13000ppm, 15000ppm, 18000ppm or 20000ppm).

[0067] In one embodiment, the ternary material includes a chemical formula of Li(Ni x Co y Mn z )O2 particles, wherein 0.5≤x≤0.95 (e.g., 0.5, 0.6, 0.7, 0.8, 0.9 or 0.95), 0.05≤y≤0.5 (e.g., 0.05, 0.1, 0.2, 0.3, 0.4 or 0.5), and 0.05≤z≤0.5 (e.g., 0.05, 0.1, 0.2, 0.3, 0.4 or 0.5).

[0068] Research has found that increasing the nickel content in ternary materials is conducive to increasing the gram capacity of ternary materials and reducing the cost per unit gram capacity; increasing the cobalt content in ternary materials is conducive to improving the rate performance of ternary materials, improving ion conductivity and reducing cation mixing; increasing the manganese content in ternary materials is conducive to improving the safety of ternary materials and reducing the overall cost of ternary materials. Based on this, controlling the weight content range x, y, z in the chemical formula within the above range can make the comprehensive performance of ternary materials better.

[0069] In one example, the ternary material includes particles with a layered structure. In this case, the ion transmission rate of the ternary material is faster, which is beneficial to reducing the transmission impedance of the battery.

[0070] In one example, the ternary material has a layered structure.

[0071] In one embodiment, the ternary material includes a chemical formula of Li(Ni x Co y Mn 1-x )O2 particles, wherein 0.5≤x≤0.95, 0.05≤y≤0.5, the average particle size D1 of the ternary material is 5μm≤D1≤15μm, and the specific surface area of ​​the ternary material is 0.3m 2 / g-1m 2 / g, the ternary material has a layered structure.

[0072] In one example, the lithium cobalt oxide material includes a chemical formula of LiCoM x O2 particles, the average particle size D2 of the lithium cobalt oxide material is 10 μm ≤ D2 ≤ 20 μm, and the specific surface area of ​​the lithium cobalt oxide material is 0.07 m 2 / g-0.32m 2 / g, and the crystal structure of the lithium cobalt oxide material is single crystal.

[0073] In one example, based on the total weight of the first positive electrode active layer, the weight content of the ternary material is 95%-99% (eg, 95%, 96%, 97%, 98% or 99%).

[0074] In one example, based on the total weight of the first positive electrode active layer, the weight content of the ternary material is 96.2%-97.8%.

[0075] In one example, based on the total weight of the second positive electrode active layer, the weight content of the lithium cobalt oxide material is 94%-99% (eg, 94%, 95%, 96%, 97%, 98% or 99%).

[0076] In one example, based on the total weight of the second positive electrode active layer, the weight content of the lithium cobalt oxide material is 96%-98%.

[0077] In one example, based on the sum of the weights of the ternary material and the lithium cobalt oxide material, the weight content of the ternary material and the weight content of the lithium cobalt oxide material are in the ratio of (5%-95%): (95%-5%) (for example, 5%:95%, 10%:90%, 20%:80%, 30%:70%, 40%:60%, 50%:50%, 60%:40%, 70%:30%, 80%:20%, 90%:10% or 95%:5%). It is understandable that the weight content of the ternary material can be in the range of 5%-95%, and the weight content of the lithium cobalt oxide material can be in the range of 95%-5%, but it needs to be satisfied that the sum of the weight content of the ternary material and the weight content of the lithium cobalt oxide material is 100%.

[0078] In one example, at any two positions in the positive electrode active material layer, the difference in the weight content of the ternary material per unit area of ​​the positive electrode active material layer is less than 0.6% (e.g., 0.55%, 0.5%, 0.4%, 0.3%, 0.2%, 0.1%, 0.05% or 0.01%), and the difference in the weight content of the lithium cobalt oxide material per unit area of ​​the positive electrode active material layer is less than 0.6% (e.g., 0.55%, 0.5%, 0.4%, 0.3%, 0.2%, 0.1%, 0.05% or 0.01%). Fig.10 As shown, at this time, the ternary material and the lithium cobalt oxide material are distributed more evenly in the positive electrode active material layer.

[0079] The weight content of the ternary material in the positive electrode active material layer per unit area is the weight content of the ternary material based on the total weight of the positive electrode active material layer per unit area. The weight content of the lithium cobalt oxide material in the positive electrode active material layer per unit area is the weight content of the lithium cobalt oxide material based on the total weight of the positive electrode active material layer per unit area. The specific test method is as follows: take the positive electrode active material layer at any two positions (for example, A and B), obtain the first positive electrode active layer and the second positive electrode active layer at A, obtain the first positive electrode active layer and the second positive electrode active layer at B, and test the ratio of nickel, cobalt and manganese in the first positive electrode active layer at A by ICP to obtain the content of the ternary material as A1 and the content of the cobalt element in the second positive electrode active layer to obtain the content of the lithium cobalt oxide material as A2, and test the ratio of nickel, cobalt and manganese in the first positive electrode active layer at B by ICP to obtain the content of the ternary material as B1 and the content of the cobalt element in the second positive electrode active layer to obtain the content of the lithium cobalt oxide material as B2. Then |A2-A1|<0.6%, and |B2-B1|<0.6%. Taking "|A2-A1|" as an example, it means the absolute value of the difference between A2 and A1, that is, A2-A1 or A1-A2 is less than 0.6%.

[0080] In one example, the first positive electrode active layer further includes a first conductive agent and a first binder.

[0081] In one example, the first conductive agent includes at least one of a carbon black conductive agent, a graphite conductive agent, a carbon nanotube, graphene, and a conductive polymer.

[0082] In one example, the first binder includes at least one of styrene-butadiene latex, polytetrafluoroethylene, polyethylene oxide, polyvinylidene fluoride, and the like.

[0083] In one example, based on the total weight of the first positive electrode active layer, the weight content of the first conductive agent is 0.1%-3% (for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%), and the weight content of the first binder is 0.5%-5% (for example, 0.5%, 1%, 2%, 3%, 4% or 5%).

[0084] In one example, based on the total weight of the first positive electrode active layer, the weight content of the first conductive agent is 0.3%-3%, and the weight content of the first binder is 1%-5%.

[0085] In one example, the second positive electrode active layer further includes a second conductive agent and a second binder.

[0086] In one example, the second conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, metal powder, fibers, and the like.

[0087] In one example, the second binder includes at least one of styrene-butadiene latex, polytetrafluoroethylene, polyethylene oxide, polyvinylidene fluoride, and the like.

[0088] In one example, based on the total weight of the second positive electrode active layer, the weight content of the second conductive agent is 0.5%-5% (for example, 0.5%, 1%, 2%, 3%, 4% or 5%), and the weight content of the second binder is 0.3%-4.5% (for example, 0.3%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or 4.5%).

[0089] In one example, based on the total weight of the second positive electrode active layer, the weight content of the second conductive agent is 0.2%-3%, and the weight content of the second binder is 1%-4%.

[0090] In one example, the CB value of the bend zone of the wound battery cell is 1.05-1.25 (e.g., 1.05, 1.1, 1.15, 1.2 or 1.25). Controlling the CB value of the bend zone of the wound battery cell within the above range can improve the problem of lithium deposition in the bend zone, thereby improving the safety performance of the battery.

[0091] The CB value of the bending area of ​​the wound battery cell = gram capacity of negative electrode active material × surface density of negative electrode sheet × weight content of negative electrode active material in negative electrode active material layer / (gram capacity of ternary material × surface density of recessed area × weight content of ternary material in positive electrode active material layer in recessed area + gram capacity of lithium cobalt oxide material × surface density of recessed area × weight content of lithium cobalt oxide material in positive electrode active material layer in recessed area). The surface density of the recessed area is the mass of positive electrode active material layer per unit area.

[0092] In one example, the width of the recessed area is 5 mm-20 mm (for example, 5 mm, 8 mm, 10 mm, 12 mm, 15 mm, 18 mm or 20 mm); the width of the recessed area represents the shortest distance along the length direction of the positive electrode sheet that the projection of the recessed area on the positive electrode sheet can completely cover all the recesses.

[0093] In one example, the depth h of the recessed portion is less than the thickness H of the positive electrode active material layer.

[0094] In one example, the depth h of the recess is 1 μm-50 μm (e.g., 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 13 μm, 15 μm, 17 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm). The depth of the recess is the vertical length along the thickness direction of the positive electrode sheet. When the recess is a hole, the depth of the recess is the depth of the hole. When the recess includes multiple holes (≥2), the depth of the hole is the maximum value of the depth of all holes; when the recess is a groove, the depth of the recess is the depth of the groove. When the recess includes multiple grooves (≥2), the depth of the groove is the maximum value of the depth of all grooves; when the recess includes a hole and a groove, the depth of the recess is the maximum value of the depth of the hole and the groove.

[0095] In one example, the concave portion includes one or more of a hole and a groove. The concave portion can be punched and grooved by performing laser surface scanning on the concave portion area.

[0096] In one example, the recesses are all holes.

[0097] In one example, the recesses are all grooves.

[0098] In one example, the recessed area includes at least one hole. It is understood that the number of holes in the recessed area is ≥ 1 (e.g., 15, 10, 15, 20, 30, 40, 50, 100, 500, 1000, 5000, 10000, 50000 or 100000).

[0099] The projection of the hole on the positive electrode sheet may be a circle or an ellipse.

[0100] In one example, the depth of the hole is 1 μm-50 μm (e.g., 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 13 μm, 15 μm, 17 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm). The depth of the hole is the vertical length along the thickness direction of the positive electrode sheet. When the recess includes one hole, the depth of the hole is the depth of the hole; when the recess includes at least two holes, the depth of the hole is the depth of any one of the holes.

[0101] In one example, the diameter of the hole is 20 μm-200 μm (for example, 20 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm or 200 μm). When the projection of the hole on the positive electrode sheet is a circle, the diameter of the hole is the diameter of the circle. When the projection of the hole on the positive electrode sheet is an ellipse, the diameter of the hole is the maximum distance between any two points on the ellipse. When the recess includes one hole, the diameter of the hole is the diameter of the hole; when the recess includes at least two holes, the diameter of the hole is the diameter of any one of the holes.

[0102] In one example, the spacing of the holes is 20 μm-5000 μm (e.g., 20 μm, 50 μm, 100 μm, 300 μm, 500 μm, 800 μm, 1000 μm, 1500 μm, 2000 μm, 2500 μm, 3000 μm, 3500 μm, 4000 μm, 4500 μm or 5000 μm). The spacing of the holes is the shortest distance between the edge lines of the projections of two adjacent holes on the positive electrode sheet.

[0103] When the number of holes in the recessed area is greater than 1, the holes may be randomly scattered or distributed in a matrix.

[0104] In one embodiment, the holes are distributed in a matrix (e.g. Figure 3 As shown in the figure, b is the length direction of the positive electrode sheet, and c is the width direction of the positive electrode sheet). This distribution is uniform and orderly, and the channels are coordinated with each other to form a more stable network channel, which improves the black spot problem caused by uneven distribution of electrolyte during the long cycle of the battery cell and improves the cycle stability of the battery.

[0105] In one example, the recessed area includes at least one groove. It is understood that the number of grooves in the recessed area is ≥ 1 (e.g., 15, 10, 15, 20, 30, 40, 50, 100, 500, 1000, 5000, 10000, 50000 or 100000).

[0106] In one example, the width D of the groove is 1 μm-500 μm (e.g., 1 μm, 5 μm, 10 μm, 30 μm, 50 μm, 80 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm or 500 μm). When the recess includes one groove, the width of the groove is the width of the groove; when the recess includes at least two grooves, the width of the groove is the width of any one of the grooves.

[0107] In the present invention, the projection of the groove on the positive electrode sheet includes two long sides, and the width of the groove is the average distance from one long side to another long side in the length direction or width direction of the positive electrode sheet. Figure 4 , Figure 5 , Figure 6 , Figure 7 and Fig.11 As shown, the two long sides of the slot are straight lines, where Figure 4 , Figure 5 and Figure 6 The two long sides of the middle groove are arranged in parallel. In this case, the distance from any point on one long side to the other long side in the length direction or width direction of the positive electrode sheet is equal. Then the width of the groove is the distance from any point on one long side to the other long side in the length direction or width direction of the positive electrode sheet. Figure 7 The two long sides of the middle slot are not set in parallel, and the distance from any point on one long side to the other long side is not equal. In this case, the width of the slot can be averaged, that is, on one long side, based on the length of the long side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the technical results more accurate), and the width corresponding to each point is measured, and the average value is taken to obtain the width of the slot; Figure 8 The two long sides of the middle slot are curves. The distance from any point on one long side to the other long side is not equal. In this case, the width of the slot can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 8 The two long sides are curves, which do not exist Figure 7 The relationship between the two long sides of the groove is determined by the method of measuring the groove. Therefore, 50 points can be randomly selected for measurement), and the width corresponding to each point is measured, and the average value is taken to obtain the width of the groove. Similarly, it is generally believed that the projection of the groove on the positive electrode sheet includes two long sides, and the width of the groove is the average distance from one long side to another long side in the length direction or width direction of the positive electrode sheet. The width of the groove can be tested by conventional means in the art, such as by SEM.

[0108] When the width of the groove is relatively small, for example, 1 μm-30 μm, the groove can be called a “line”.

[0109] In one example, the depth of the groove is 1 μm-50 μm (e.g., 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 13 μm, 15 μm, 17 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm). The depth of the groove is the vertical distance along the thickness direction of the positive electrode sheet. When the recess includes one groove, the depth of the groove is the depth of the groove; when the recess includes at least two grooves, the depth of the groove is the depth of any one of the grooves.

[0110] In one example, the pitch of the grooves is 20 μm-5000 μm (e.g., 20 μm, 50 μm, 100 μm, 300 μm, 500 μm, 800 μm, 1000 μm, 1500 μm, 2000 μm, 2500 μm, 3000 μm, 3500 μm, 4000 μm, 4500 μm, or 5000 μm).

[0111] In the present invention, the spacing of the grooves is the average distance between two adjacent long sides of two adjacent grooves on the positive electrode sheet in the length direction or width direction of the positive electrode sheet. Figure 4 and Figure 5 In the example, the two adjacent long sides of the groove are straight and parallel. Therefore, in the length direction, the distance from any point on one long side to the other long side is equal. In this case, the spacing of the grooves is the distance d from any point on one long side to the other long side in the length direction. Figure 7 In the example, the two adjacent long sides of the slot are straight lines, but not parallel. Therefore, the distance from any point on one long side to the other long side is not equal. In this case, the slot spacing can be averaged, that is, on one long side, based on the length of the long side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width corresponding to each point is measured, and the average value is taken to obtain the slot spacing; Figure 8 In the example, two adjacent long sides are curves, and the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the slots can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 8 The two long sides are curves, which do not exist Figure 7 The relationship between the two long sides of the groove can be determined by randomly selecting 50 points for measurement, measuring the width corresponding to each point, and taking the average value to obtain the spacing of the groove. The spacing of the groove can be obtained by conventional means in the art, such as by SEM.

[0112] In one embodiment, the slots are arranged in a matrix (eg Figure 4 As shown, where b is the length direction of the positive electrode sheet and c is the width direction of the positive electrode sheet).

[0113] In one embodiment, the groove runs through both side edges of the positive electrode sheet in the width direction. Figure 5 As shown, the groove runs through the two side edges of the positive electrode sheet in the width direction c.

[0114] In one embodiment, the groove does not penetrate the two side edges of the positive electrode sheet in the width direction. Figure 6 As shown, the groove does not penetrate the two side edges of the positive electrode sheet in the width direction c.

[0115] In one example, the groove occupies the entire recessed area. Fig.11 As shown, this can be achieved by local thinning.

[0116] In one example, the battery includes a negative electrode sheet, for example, the negative electrode sheet includes a negative electrode collector and a negative electrode active material layer located on one side or both sides of the negative electrode collector, and the negative electrode active material layer includes a negative electrode active material, a negative electrode conductor and a negative electrode binder.

[0117] In one example, the negative electrode active material includes a graphite mixed material and / or graphite doped with at least one of hard carbon, soft carbon, silicon oxide and silicon carbon.

[0118] In one example, the graphite includes artificial graphite and / or natural graphite.

[0119] In one example, the negative electrode active material is a graphite mixed material doped with hard carbon, wherein the weight content of the hard carbon is 2wt%-10wt% (for example, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%) based on the total weight of the graphite mixed material.

[0120] In one example, based on the total weight of the graphite mixed material, the weight content of the hard carbon is 3wt%-5wt%.

[0121] In one example, the negative electrode conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber and carbon nanotube.

[0122] In one example, the negative electrode binder includes one or more of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, polyethylene oxide, and polyvinylidene fluoride.

[0123] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 80wt%-99.5wt% (for example, 80wt%, 85wt%, 90wt%, 95wt%, 99wt%, 99.5wt%), the weight content of the negative electrode conductor is 0.25wt%-10wt% (for example, 0.25wt%, 0.5wt%, 1wt%, 3wt%, 5wt%, 7wt%, 10wt%), and the weight content of the negative electrode binder is 0.25wt%-10wt% (for example, 0.25wt%, 0.5wt%, 1wt%, 3wt%, 5wt%, 7wt%, 10wt%).

[0124] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 90wt%-99wt%, the weight content of the negative electrode conductor is 0.5wt%-5wt%, and the weight content of the negative electrode binder is 0.5wt%-5wt%.

[0125] A second aspect of the present invention provides a battery, which includes the wound battery cell described in the first aspect of the present invention.

[0126] The battery may be a lithium ion battery.

[0127] The battery may be a secondary lithium ion battery.

[0128] Since the battery includes the positive electrode sheet described in the first aspect of the present invention, the battery's liquid retention coefficient can be 1.8-2.2 (for example, 1.8, 1.9, 2, 2.1 or 2.2). At this time, the battery cell has a larger electrolyte retention capacity, which can reduce the risk of lithium precipitation, thereby further improving the safety performance of the battery.

[0129] In the present invention, the liquid retention coefficient can be tested and obtained in the following manner: testing the injection volume and extraction volume of the battery, liquid retention coefficient = (injection volume - extraction volume) / battery capacity, wherein the weight of the system before and after injection is measured using a balance, and the difference in weight of the system before and after injection is the injection volume; the weight of the system before and after extraction is measured using a balance, and the difference in weight of the system before and after extraction is the extraction volume.

[0130] In one example, the battery further includes an electrolyte, and the electrolyte includes an ether nitrile compound. The recessed portion is provided in the recessed portion area of ​​the positive electrode sheet, which destroys the integrity of the surface of the positive electrode sheet, increases the burrs on the surface of the positive electrode sheet, and the surface of the recessed portion is uneven, and the current distribution is uneven, which affects the safety performance of the battery. During the charge and discharge process, the CO bond of the ether nitrile compound undergoes an oxidation reaction, thereby forming a protective film on the positive electrode side. At the same time, the cyano group in the ether nitrile compound can also react with the cobalt ions on the positive electrode side, further improving the stability of the protective film. Therefore, through the synergistic cooperation between the positive electrode sheet and the electrolyte including the ether nitrile compound, the ether nitrile compound can form a protective film on the positive electrode surface, especially a protective film with high stability can be formed on the surface of the recessed portion and the burr surface, reducing the safety risk caused by the uneven current distribution caused by the burrs, thereby further improving the safety performance of the battery. After the ether nitrile compound forms a film on the surface of the positive electrode material, the surface of the positive electrode material is relatively smooth, the specific surface area is reduced, and the impedance of the interface is reduced.

[0131] In one example, based on the total weight of the electrolyte, the weight content y% of the ether nitrile compound is 3%-15% (for example, 3%, 5%, 8%, 10%, 12% or 15%). When the weight content of the ether nitrile compound in the electrolyte is lower than 3%, the amount of the ether nitrile compound is too small to provide good protection for the positive electrode side; when the weight content of the ether nitrile compound in the electrolyte is higher than 15%, the amount of the ether nitrile compound is too high, which is easy to increase the impedance of the battery and increase the risk of lithium deposition or battery diving.

[0132] In one example, the ether nitrile compound includes one or more of tetraethylene glycol di(2-cyanoethyl) ether, ethylene glycol di(4-cyanobutyl) ether, and ethylene glycol (bis) propionitrile ether.

[0133] In one example, the battery satisfies the following relationship: 0.03≤y-0.21h≤3.16 (for example, 0.03, 0.05, 0.1, 0.5, 1, 1.5, 2, 2.53 or 3.16). Controlling the battery to satisfy the above formula can achieve a higher adaptation of the content of the ether nitrile compound in the electrolyte and the depth of the recess, so that the weight content of the ether nitrile compound can meet the requirement of forming a protective film on the surface of the recess, thereby maximally improving the electrolyte bridge breaking problem caused by excessive consumption of ether nitrile compounds in the electrolyte in the recess area during the battery cell cycle. When y-0.21h<0.03, the weight content of the ether nitrile compound in the electrolyte is too low or the depth of the recess is too large, resulting in the need to consume more ether nitrile compounds to ensure that the protective film formed covers the surface of the recess. The problem of electrolyte bridge breaking caused by the consumption of more ether nitrile compounds affects the battery's cycle performance. When y-0.21h>3.16, the amount of the remaining ether nitrile compound in the electrolyte is too much, which increases the internal resistance of the battery and reduces the cycle stability of the battery.

[0134] In one example, the electrolyte further includes a lithium salt, an organic solvent and an additive.

[0135] In one example, the lithium salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate) (LiBOB), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium and lithium bis(trifluoromethylsulfonyl)imide.

[0136] In one example, the organic solvent includes at least one selected from carbonate esters and carboxylic acid esters.

[0137] In one example, the carbonate includes at least one of fluorinated or unsubstituted ethylene carbonate, fluorinated or unsubstituted propylene carbonate, fluorinated or unsubstituted dimethyl carbonate, fluorinated or unsubstituted diethyl carbonate, and fluorinated or unsubstituted ethyl methyl carbonate.

[0138] In one example, the carboxylic acid ester includes at least one of fluoro or unsubstituted propyl acetate, fluoro or unsubstituted n-butyl acetate, fluoro or unsubstituted isobutyl acetate, fluoro or unsubstituted n-pentyl acetate, fluoro or unsubstituted isopentyl acetate, fluoro or unsubstituted propyl propionate, fluoro or unsubstituted ethyl propionate, fluoro or unsubstituted methyl butyrate, and fluoro or unsubstituted ethyl n-butyrate.

[0139] In one example, the additive includes at least one of vinylene carbonate (VC), 1,3-trihydrotetrafluoropropanol (TFP), and 4-chloro-4-hydroxybenzophenone (CHB).

[0140] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 5%-20%, the weight content of the organic solvent is 75%-85%, and the weight content of the additive is 1%-5%.

[0141] In one example, the battery further includes adhesive tape, which can prevent the battery cell from short-circuiting and prevent the battery cell tabs from deforming or loosening. The battery cell will vibrate and collide during use. If the tabs are not covered with adhesive tape, they may come into contact with other devices to cause a short-circuit failure, or even cause a fire or explosion. Therefore, affixing adhesive tape can effectively prevent the battery cell tabs from coming into contact with other devices to cause a short-circuit. The battery cell tabs need to be subjected to a certain force when connected. If the force is uneven or too small, the tabs may be deformed or loosened, which will cause the battery's electrical performance to decline and affect the battery's life and performance.

[0142] In one embodiment, the adhesive tape comprises a substrate and an adhesive layer located on one or both sides of the substrate. Fig. 9 As shown, the adhesive tape 2 includes a substrate 21 and an adhesive layer 22 located on one side surface of the substrate 21 .

[0143] In one example, the substrate includes one or more of polyethylene terephthalate (PET), polyimide (PI) and polyolefin (PO).

[0144] The polyolefin may include one or more of polyethylene, polypropylene, and polyisobutylene.

[0145] In one embodiment, the adhesive layer includes one or more of polyacrylate, rubber, polyurethane and organic silicone.

[0146] In one example, the adhesive layer is rubber.

[0147] In one example, the rubber includes one or more of polyisobutylene, polypropylene, styrene-butadiene rubber, styrene-butadiene-styrene terblock copolymer (SBS), and styrene-isoprene-styrene block copolymer (SIS).

[0148] Research has found that the adhesive layer in the adhesive tape easily absorbs electrolyte and swells at high temperature, causing the thickness of the adhesive tape body to increase, and the adhesive tape gradually loses adhesion, becomes hard and brittle. If the broken adhesive tape is at the end of the positive electrode, it will cause the side of the battery cell to have ridges; if the broken adhesive tape is at the tab, it will cause black spots and lithium deposition at the interface of the negative and anode tabs, which may cause safety risks in severe cases. In addition, while swelling, the polymer in the adhesive layer is easily dissolved and transferred into the electrolyte. The polymer entering the electrolyte will have a certain impact on the binder in the positive electrode active material layer, causing the positive electrode active material layer to fall off, and the dissolved polymer will also slowly move to the diaphragm and the negative electrode sheet with the electrolyte, thereby affecting the transmission of lithium ions and causing lithium deposition on the negative electrode side.

[0149] The present invention optimizes the polymer of the adhesive layer in the adhesive tape so that the adhesive layer includes a specific substance (polyolefin), thereby reducing the swelling rate and solubility of the adhesive tape in the electrolyte. On the one hand, the properties of the adhesive tape itself, such as adhesion, can be maintained to ensure the stability of the battery structure; on the other hand, the occurrence of side reactions with the electrolyte can be reduced to ensure the stability of the battery system. At the same time, the ether nitrile compound in the electrolyte can also form a protective film on the surface of the positive electrode. By controlling the oxygen element in the inner layer of the positive electrode protective film, the risk of the adhesive tape being swollen by the oxidant is reduced, the problem of lithium deposition on the negative electrode side is improved, and the safety performance of the battery is improved.

[0150] In one example, the substrate includes one or more of polyethylene terephthalate, polyimide (PI) and polyolefin (PO), and the adhesive layer is rubber.

[0151] In one example, the thickness of the substrate is 10 μm-15 μm (eg, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm).

[0152] In one example, the thickness of the glue layer is 1 μm-8 μm (eg, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm).

[0153] In one example, the swelling rate t of the adhesive tape in the electrolyte is t≤15% (for example, 15%, 10%, 5%, 1%, 0.5% or 0.1%). The swelling rate of the adhesive tape in the electrolyte (wherein the electrolyte may be a conventional electrolyte in the art or the electrolyte described in the present invention) may be tested in the following manner: immerse the adhesive tape in the electrolyte and store it at 85°C, record the initial weight of the adhesive tape as m1, weigh it after 7 days, record the weight after 7 days as m2, and the swelling rate t=(m2-m1) / m1.

[0154] By controlling the swelling rate of the adhesive tape in the electrolyte within the above range, the structural stability of the adhesive tape can be improved, and the risk of battery safety problems caused by the swelling of the adhesive tape can be reduced, thereby further improving the safety performance of the battery.

[0155] In one example, the dissolution rate p of the adhesive tape in the electrolyte is p≤10% (for example, 10%, 5%, 1%, 0.5% or 0.1%). The dissolution rate of the adhesive tape in the electrolyte can be tested in the following manner: soak the adhesive tape in an electrolyte (wherein the electrolyte can be a conventional electrolyte in the art or the electrolyte described in the present invention) and store it at 25°C, record the initial weight of the adhesive tape as n1, take out the adhesive tape after 7 days and dry it (bake at 85°C for 6 hours), record the mass of the adhesive tape before and after baking, and record them as n2 and n3 respectively, and the dissolution rate of the adhesive tape in the electrolyte p=(n1-n3) / n1.

[0156] By controlling the solubility of the adhesive tape in the electrolyte within the above range, the safety risk caused by the polymer in the adhesive tape entering the electrolyte can be reduced, thereby further improving the safety performance of the battery.

[0157] In one example, the swelling rate t of the adhesive tape in the electrolyte is t≤15%, and the dissolution rate p of the adhesive tape in the electrolyte is p≤10%.

[0158] In one example, the battery is a lithium-ion battery.

[0159] Since the battery of the present invention comprises the wound battery core of the present invention, the cycle stability of the battery is improved, the safety performance is improved, the service life is prolonged, and the expansion rate is reduced.

[0160] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0161] The following examples are provided to illustrate the batteries of the present invention.

[0162] Example 1

[0163] (1) Preparation of positive electrode

[0164] Positive electrode current collector: aluminum foil;

[0165] First positive electrode active material layer: ternary material (wherein the chemical formula is Li(Ni 0.7 Co 0.1 Mn 0.2 )O2 particles, the average particle size D1 is 6μm, and the specific surface area is 0.65m 2 / g), 20 parts by weight, a first conductive agent, conductive carbon black, and a first binder, polyvinylidene fluoride, wherein the weight ratio of the ternary material: the first conductive agent: the first binder is 96.5:2:1.5;

[0166] Second positive electrode active material layer: lithium cobalt oxide material (wherein the chemical formula is LiCoMg 0.7 The average particle size D2 of O2 is 13 μm and the specific surface area is 0.35 m 2 / g, the crystal structure is single crystal, the weight content of M element in the lithium cobalt oxide material is 300ppm), 80 parts by weight, conductive carbon black as the second conductive agent, and polyvinylidene fluoride as the second binder, wherein the weight ratio of lithium cobalt oxide material: second conductive agent: second binder is 96.5:2:1.5.

[0167] The ternary material, the first conductive agent and the first binder are added into a stirring tank, and NMP solvent is added, and the mixture is fully stirred according to a known batching process, and passed through a 200-mesh sieve to prepare a first positive electrode slurry;

[0168] The lithium cobalt oxide material, the second conductive agent and the second binder are added to a stirring tank, and NMP solvent is added, and the mixture is fully stirred according to a known batching process, and passed through a 200-mesh sieve to prepare a second positive electrode slurry;

[0169] Use a coating machine to coat the positive electrode slurry according to Figure 1Coated onto the positive electrode current collector (wherein, the first positive electrode slurry is coated on both sides of the positive electrode current collector to form a first positive electrode active layer (wherein, the thickness of the first positive electrode active layer h1 is 25 μm), and the second positive electrode slurry is coated on the surface of the first positive electrode active layer to form a second positive electrode active layer (wherein, the second positive electrode active layer h2 is 80 μm), and then dried and rolled (see Fig.10 (a) and Fig.10 (b)) and slitting; the slitting positive electrode sheets are Figure 2 Laser surface scanning is performed (wherein the width of the concave area is 10 mm, the depth of the concave h is 6 μm, the concave is a hole, the depth of the hole is 5.81 μm, the diameter of the hole is 7.18 μm, the spacing of the holes is 150 μm, and the holes are distributed in a matrix). After laser surface scanning, the positive electrode sheet is cleaned, the pole ear is welded and the adhesive tape is pasted to obtain a positive electrode sheet, wherein the thickness of the positive electrode active material layer is H=h1+h2=105 μm; at any two positions in the positive electrode active material layer, the difference in the weight content of the ternary material per unit area in the positive electrode active material layer is 0.23%, and the difference in the weight content of the lithium cobalt oxide material per unit area in the positive electrode active material layer is 0.36%; the positive electrode sheet satisfies 0.01H≤h≤0.5H-0.01, and h1+h2*D2 / D1=25+80*13 / 6=198.3.

[0170] (2) Preparation of negative electrode

[0171] Negative electrode current collector: copper foil;

[0172] Negative electrode active material layer: 98.2 parts by weight of negative electrode active material (artificial graphite), 0.6 parts by weight of negative electrode conductive agent (carbon nanotube), 1.2 parts by weight of negative electrode binder (styrene-butadiene latex);

[0173] Add the negative electrode active material, negative electrode conductive agent and negative electrode binder into a stirring tank, add deionized water solvent, stir thoroughly according to the known batching process, pass through a 150-mesh screen to prepare the negative electrode slurry. Use a coating machine to apply the negative electrode slurry to the surfaces of both sides of the negative electrode current collector in a known coating method to form a negative electrode active material layer, dry it at 100°C, and then roll-cut, clean, weld the tabs and tape the negative electrode sheets to finally obtain the required negative electrode sheets.

[0174] (3) Preparation of electrolyte

[0175] Lithium salt: lithium hexafluorophosphate, 14.5 parts by weight;

[0176] Ether nitrile compound: ethylene glycol (bis) propionitrile ether, 3.5 parts by weight (y%=3.5%, y-0.21h=3.5-0.21*6=2.24);

[0177] Organic solvent: propyl propionate (PP), 30 parts by weight, ethylene carbonate (EC), 20 parts by weight, fluoroethylene carbonate (FEC), 10 parts by weight, dimethyl carbonate (DMC), 20 parts by weight;

[0178] Additives: 1,3-trihydrotetrafluoropropanol (TFP), 2 parts by weight;

[0179] In a glove box (H2O < 0.01ppm, O2 < 0.01ppm, Ar atmosphere), the organic solvents are mixed evenly, and then fully dried lithium salt is added thereto. After dissolution, additives and ether nitrile compounds are added and stirred evenly. After passing the moisture and free acid tests, the desired electrolyte is obtained.

[0180] (4) Diaphragm

[0181] Polyethylene material is used as the diaphragm base membrane with a thickness of 5μm; one side of the diaphragm base membrane is coated with a ceramic layer, and the ceramic layer is coated with a PMMA+PVDF mixture (wherein the weight ratio of PMMA to PVDF is 1:1); the other side of the diaphragm base membrane and the surface of the ceramic layer are coated with a non-ceramic layer, and the non-ceramic layer is coated with PMMA (wherein the polyethylene diaphragm base membrane, PMMA and PVDF are all commercially purchased).

[0182] (5) Adhesive tape

[0183] Substrate: polyethylene terephthalate, thickness 12 μm;

[0184] Adhesive layer: polyisobutylene, thickness 4μm;

[0185] The adhesive layer is coated on both sides of the substrate. The swelling rate t% of the adhesive paper in the electrolyte of step (3) is 8.36%, and the dissolution rate p% is 7.36%.

[0186] (6) Preparation of lithium-ion batteries

[0187] The positive electrode sheet of step (1), the negative electrode sheet of step (2) and the separator of step (4) are wound together to form a wound battery cell (wherein the number of bending areas is 23, the CB value of the bending areas is 1.11, and the number of concave areas is 23), wherein the separator is located between the positive electrode sheet and the negative electrode sheet. Subsequently, the battery is packaged with an aluminum plastic film, baked to remove moisture, and then the electrolyte of step (3) is injected. Subsequently, after treatments such as formation and secondary sealing, a lithium ion battery is obtained, and the liquid retention coefficient of the lithium ion battery is 1.97.

[0188] Example 2

[0189] (1) Preparation of positive electrode

[0190] Positive electrode current collector: aluminum foil;

[0191] First positive electrode active material layer: ternary material (wherein the chemical formula is Li(Ni 0.7 Co 0.1 Mn 0.2 )O2 particles, the average particle size D1 is 6μm, and the specific surface area is 0.65m 2 / g), 20 parts by weight, a first conductive agent, conductive carbon black, and a first binder, polyvinylidene fluoride, wherein the weight ratio of the ternary material: the first conductive agent: the first binder is 96.5:2:1.5;

[0192] Second positive electrode active material layer: lithium cobalt oxide material (wherein the chemical formula is LiCoMg 0.7 The average particle size D2 of O2 is 13 μm and the specific surface area is 0.35 m 2 / g, the crystal structure is single crystal, the weight content of M element in the lithium cobalt oxide material is 300ppm), 80 parts by weight, conductive carbon black as the second conductive agent, and polyvinylidene fluoride as the second binder, wherein the weight ratio of lithium cobalt oxide material: second conductive agent: second binder is 96.5:2:1.5.

[0193] The ternary material, the first conductive agent and the first binder are added into a stirring tank, and NMP solvent is added, and the mixture is fully stirred according to a known batching process, and passed through a 200-mesh sieve to prepare a first positive electrode slurry;

[0194] The lithium cobalt oxide material, the second conductive agent and the second binder are added to a stirring tank, and NMP solvent is added, and the mixture is fully stirred according to a known batching process, and passed through a 200-mesh sieve to prepare a second positive electrode slurry;

[0195] Use a coating machine to coat the positive electrode slurry according to Figure 1 Coated onto the positive electrode current collector (wherein, the first positive electrode slurry is coated on both sides of the positive electrode current collector to form a first positive electrode active layer (wherein, the thickness of the first positive electrode active layer h1 is 25 μm), and the second positive electrode slurry is coated on the surface of the first positive electrode active layer to form a second positive electrode active layer (wherein, the second positive electrode active layer h2 is 80 μm), and then dried and rolled (see Fig.10 (a) and Fig.10 (b)) and slitting; the slitting positive electrode sheets are Figure 2Laser surface scanning is performed (wherein the width of the concave area is 10 mm, the depth h of the concave is 6 μm, the concave is a groove, the depth of the groove is 5.85 μm, the width of the groove is 8.12 μm, the spacing of the groove is 100 μm, and the grooves are distributed in a matrix). After laser surface scanning, the positive electrode sheet is cleaned, the pole ear is welded and the adhesive tape is pasted to obtain a positive electrode sheet, wherein the thickness of the positive electrode active material layer is H=h1+h2=105 μm; at any two positions in the positive electrode active material layer, the difference in the weight content of the ternary material per unit area in the positive electrode active material layer is 0.23%, and the difference in the weight content of the lithium cobalt oxide material per unit area in the positive electrode active material layer is 0.36%; the positive electrode sheet satisfies 0.01H≤h≤0.5H-0.01, and h1+h2*D2 / D1=25+80*13 / 6=198.3.

[0196] (2) The negative electrode sheet was prepared in the same manner as in Example 1.

[0197] (3) The preparation of the electrolyte is carried out according to Example 1.

[0198] (4) Diaphragm: refer to Example 1.

[0199] (5) Adhesive tape: refer to Example 1.

[0200] (6) Preparation of lithium-ion batteries

[0201] The positive electrode sheet of step (1), the negative electrode sheet of step (2) and the separator of step (4) are wound together to form a wound battery cell (wherein the number of bending areas is 23, the CB value of the bending areas is 1.12, and the number of concave areas is 23), wherein the separator is located between the positive electrode sheet and the negative electrode sheet. Subsequently, the battery is packaged with an aluminum plastic film, baked to remove moisture, and then the electrolyte of step (3) is injected. Subsequently, after treatments such as formation and secondary sealing, a lithium ion battery is obtained. The liquid retention coefficient of the lithium ion battery is 2.04.

[0202] Example 3

[0203] (1) Preparation of positive electrode

[0204] Positive electrode current collector: aluminum foil;

[0205] First positive electrode active material layer: ternary material (wherein the chemical formula is Li(Ni 0.7 Co 0.1 Mn 0.2 )O2 particles, the average particle size D1 is 6μm, and the specific surface area is 0.65m 2 / g), 20 parts by weight, a first conductive agent, conductive carbon black, and a first binder, polyvinylidene fluoride, wherein the weight ratio of the ternary material: the first conductive agent: the first binder is 96.5:2:1.5;

[0206] Second positive electrode active material layer: lithium cobalt oxide material (wherein the chemical formula is LiCoMg 0.7 The average particle size D2 of O2 is 13 μm and the specific surface area is 0.35 m 2 / g, the crystal structure is single crystal, the weight content of M element in the lithium cobalt oxide material is 300ppm), 80 parts by weight, conductive carbon black as the second conductive agent, and polyvinylidene fluoride as the second binder, wherein the weight ratio of lithium cobalt oxide material: second conductive agent: second binder is 96.5:2:1.5.

[0207] The ternary material, the first conductive agent and the first binder are added into a stirring tank, and NMP solvent is added, and the mixture is fully stirred according to a known batching process, and passed through a 200-mesh sieve to prepare a first positive electrode slurry;

[0208] The lithium cobalt oxide material, the second conductive agent and the second binder are added to a stirring tank, and NMP solvent is added, and the mixture is fully stirred according to a known batching process, and passed through a 200-mesh sieve to prepare a second positive electrode slurry;

[0209] Use a coating machine to coat the positive electrode slurry according to Figure 1 Coated onto the positive electrode current collector (wherein, the first positive electrode slurry is coated on both sides of the positive electrode current collector to form a first positive electrode active layer (wherein, the thickness of the first positive electrode active layer h1 is 25 μm), and the second positive electrode slurry is coated on the surface of the first positive electrode active layer to form a second positive electrode active layer (wherein, the second positive electrode active layer h2 is 80 μm), and then dried and rolled (see Fig.10 (a) and Fig.10 (b)) and slitting; the slitting positive electrode sheets are Figure 2 Laser surface scanning was performed (wherein the width of the concave area was 10 mm, the depth h of the concave was 6 μm, the concave areas were holes and grooves, the depth of the holes was 5.67 μm, the diameter of the holes was 7.18 μm, the spacing between the holes was 150 μm, the depth of the grooves was 5.98 μm, the width of the grooves was 8.12 μm, the spacing between the grooves was 100 μm, and the holes and grooves were distributed in a matrix). After laser surface scanning, the positive electrode sheet is cleaned, the ear is welded and the adhesive tape is pasted to obtain the positive electrode sheet, wherein the thickness of the positive electrode active material layer is H=h1+h2=105μm; at any two positions in the positive electrode active material layer, the difference in weight content of the ternary material per unit area of ​​the positive electrode active material layer is 0.23%, and the difference in weight content of the lithium cobalt oxide material per unit area of ​​the positive electrode active material layer is 0.36%; the positive electrode sheet satisfies 0.01H≤h≤0.5H-0.01, and h1+h2*D2 / D1=25+80*13 / 6=198.3.

[0210] (2) The negative electrode sheet was prepared in the same manner as in Example 1.

[0211] (3) The preparation of the electrolyte is carried out according to Example 1.

[0212] (4) Diaphragm: refer to Example 1.

[0213] (5) Adhesive tape: refer to Example 1.

[0214] (6) Preparation of lithium-ion batteries

[0215] The positive electrode sheet of step (1), the negative electrode sheet of step (2) and the separator of step (4) are wound together to form a wound battery cell (wherein the number of bending areas is 23, the CB value of the bending areas is 1.17, and the number of concave areas is 23), wherein the separator is located between the positive electrode sheet and the negative electrode sheet. Subsequently, the battery is packaged with an aluminum plastic film, baked to remove moisture, and then the electrolyte of step (3) is injected. Subsequently, after treatments such as formation and secondary sealing, a lithium-ion battery is obtained. The liquid retention coefficient of the lithium-ion battery is 2.16.

[0216] Example 4 Group

[0217] This group of embodiments is used to illustrate the impact of changes in the "average particle size D2 of the lithium cobalt oxide material".

[0218] This group of examples is carried out with reference to Example 1, except that the average particle size D2 of the lithium cobalt oxide material is changed, as follows:

[0219] Example 4a: The average particle size D2 of the lithium cobalt oxide material is 18 μm and the specific surface area is 0.2 m 2 / g, corresponding h1+h2*D2 / D1=265;

[0220] Example 4b: The average particle size D2 of the lithium cobalt oxide material is 25 μm, and the specific surface area is 0.18 m 2 / g, corresponding h1+h2*D2 / D1=358.3;

[0221] Example 4c: The average particle size D2 of the lithium cobalt oxide material is 30 μm, and the specific surface area is 0.15 m 2 / g, corresponding h1+h2*D2 / D1=425;

[0222] Example 4d: The average particle size D2 of the lithium cobalt oxide material is 9 μm, and the specific surface area is 0.3 m 2 / g, corresponding h1+h2*D2 / D1=145.

[0223] Example 5 Group

[0224] This group of embodiments is used to illustrate the impact of changes in the "average particle size D1 of the ternary material".

[0225] This group of examples is carried out with reference to Example 1, except that the average particle size D1 of the ternary material is changed, as follows:

[0226] Example 5a: The average particle size D1 of the ternary material is 15 μm and the specific surface area is 0.63 m 2 / g, corresponding h1+h2*D2 / D1=94;

[0227] Example 5b: The average particle size D1 of the ternary material is 20 μm, and the specific surface area is 0.61 m 2 / g, corresponding h1+h2*D2 / D1=77.

[0228] Example 6 Group

[0229] This group of embodiments is used to illustrate the influence of changes in “the thickness h1 of the first positive electrode active layer and / or the thickness h2 of the second positive electrode active layer and / or the depth h of the recess”.

[0230] This group of examples is carried out with reference to Example 1, except that the thickness h1 of the first positive electrode active layer and / or the thickness h2 of the second positive electrode active layer and / or the depth h of the concave portion are changed, as follows:

[0231] Embodiment 6a: The thickness h1 of the first positive electrode active layer is 50 μm, the thickness h2 of the second positive electrode active layer is 80 μm (the thickness H of the corresponding positive electrode active material layer is 130 μm), the depth h of the concave portion is 6 μm, y-0.21*h=2.24, and the corresponding h1+h2*D2 / D1=223.3;

[0232] Embodiment 6b: The thickness h1 of the first positive electrode active layer is 120 μm, the thickness h2 of the second positive electrode active layer is 80 μm (the thickness H of the corresponding positive electrode active material layer is 200 μm), the depth h of the concave portion is 6 μm, y-0.21*h=2.24, and the corresponding h1+h2*D2 / D1=293.3;

[0233] Embodiment 6c: The thickness h1 of the first positive electrode active layer is 220 μm, the thickness h2 of the second positive electrode active layer is 80 μm (the thickness H of the corresponding positive electrode active material layer is 300 μm), the depth h of the concave portion is 6 μm, y-0.21*h=2.24, and the corresponding h1+h2*D2 / D1=393.3;

[0234] Embodiment 6d: The thickness h1 of the first positive electrode active layer is 70 μm, the thickness h2 of the second positive electrode active layer is 10 μm (the thickness H of the corresponding positive electrode active material layer is 80 μm), the depth h of the concave portion is 15 μm, and the corresponding h1+h2*D2 / D1=91.7, y-0.21*h=0.35;

[0235] Embodiment 6e: The thickness h1 of the first positive electrode active layer is 25 μm, the thickness h2 of the second positive electrode active layer is 50 μm (the thickness H of the corresponding positive electrode active material layer is 75 μm), the depth h of the concave portion is 6 μm, y-0.21*h=2.24, and the corresponding h1+h2*D2 / D1=133.3;

[0236] Embodiment 6f: The thickness h1 of the first positive electrode active layer is 25 μm, the thickness h2 of the second positive electrode active layer is 160 μm (the thickness H of the corresponding positive electrode active material layer is 185 μm), the depth h of the concave portion is 6 μm, y-0.21*h=2.24, and the corresponding h1+h2*D2 / D1=371.7;

[0237] Embodiment 6g: The thickness h1 of the first positive electrode active layer is 25 μm, the thickness h2 of the second positive electrode active layer is 80 μm (the thickness H of the corresponding positive electrode active material layer is 105 μm), the depth h of the concave portion is 34 μm, and the corresponding h1+h2*D2 / D1=198.3, and in order to reduce the influence of y-0.21*h, y is adjusted to 9.4, then y-0.21*h=2.26;

[0238] Example 6h: The thickness h1 of the first positive electrode active layer is 25 μm, the thickness h2 of the second positive electrode active layer is 80 μm (the corresponding thickness H of the positive electrode active material layer is 105 μm), the depth h of the recess is 52 μm, and the corresponding h1+h2*D2 / D1=198.3. In order to reduce the influence of y-0.21*h, y is adjusted to 13.2, then y-0.21*h=2.28.

[0239] Example 7 Group

[0240] This group of embodiments is used to illustrate the impact of changes in "the ratio of the weight content of the ternary material to the weight content of the lithium cobalt oxide material, based on the sum of the weights of the ternary material and the lithium cobalt oxide material".

[0241] This group of examples is carried out with reference to Example 1, except that the weight ratio of the ternary material to the lithium cobalt oxide material is changed to the sum of the weights of the ternary material and the lithium cobalt oxide material, as follows:

[0242] Embodiment 7a: Based on the sum of the weights of the ternary material and the lithium cobalt oxide material, the weight content of the ternary material and the weight content of the lithium cobalt oxide material is 60%:40%;

[0243] Embodiment 7b: Based on the sum of the weights of the ternary material and the lithium cobalt oxide material, the weight content of the ternary material and the weight content of the lithium cobalt oxide material is 50%:50%;

[0244] Example 7c: Based on the sum of the weights of the ternary material and the lithium cobalt oxide material, the ratio of the weight content of the ternary material to the weight content of the lithium cobalt oxide material is 90%:10%.

[0245] Example 8

[0246] The process is carried out in accordance with Example 1, except that the crystal structure of the lithium cobalt oxide material is adjusted to polycrystalline.

[0247] Example 9 Group

[0248] This group of examples is used to illustrate the impact of changes in "the weight content of ether nitrile compounds in the electrolyte, y %".

[0249] This group of examples is carried out with reference to Example 1, except that the weight content of the ether nitrile compound in the electrolyte is changed to y%, specifically as follows:

[0250] Example 9a: The weight content y% of the ether nitrile compound in the electrolyte is 0;

[0251] Example 9b: The weight content y% of the ether nitrile compound in the electrolyte is 5%, y-0.21*h=3.74;

[0252] Example 9c: The weight content y% of the ether nitrile compound in the electrolyte is 2%, y-0.21*h=0.74;

[0253] Example 9d: The weight content y% of the ether nitrile compound in the electrolyte is 15%. In order to reduce the influence of y-0.21*h, h is adjusted to 57μm, and correspondingly h2 is adjusted to 150μm, h1 is adjusted to 50μm, and H is 200μm. Correspondingly, h1+h2*D2 / D1=375, y-0.21*h=3.03.

[0254] Example 10 Group

[0255] This group of examples is used to illustrate the impact of changes in the "specific selection of the ether nitrile compound".

[0256] This group of examples is carried out with reference to Example 1, except that the specific selection of the ether nitrile compound is changed, as follows:

[0257] Embodiment 10a: The ether nitrile compound is tetraethylene glycol di(2-cyanoethyl) ether;

[0258] Example 10b: The ether nitrile compound is ethylene glycol di(4-cyanobutyl) ether.

[0259] Example 11 Group

[0260] This group of embodiments is used to illustrate the impact of changes in "tape".

[0261] This group of examples is carried out with reference to Example 1, except that the adhesive tape is changed, as follows:

[0262] Example 11a: The adhesive layer of the adhesive tape is composed of silica gel, and the swelling rate t% of the adhesive tape in the electrolyte is 20.47, and the dissolution rate p% is 15.64%;

[0263] Example 11b: The adhesive layer of the adhesive tape is composed of silica gel, the swelling t% of the adhesive tape in the electrolyte is 21.45, the dissolution rate p% is 16.54%, and the weight content y% of the ether nitrile compound in the electrolyte is 0;

[0264] Example 11c: The base material of the adhesive tape is polyimide, the adhesive layer is styrene-butadiene rubber, the swelling t% of the adhesive tape in the electrolyte is 5.13, and the dissolution rate p% is 4.78%;

[0265] Example 11d: The base material of the adhesive tape is polyethylene, the adhesive layer is styrene-butadiene rubber, the swelling rate t% of the adhesive tape in the electrolyte is 3.97, and the dissolution rate p% is 4.84%.

[0266] Example 12 Group

[0267] This group of embodiments is used to illustrate the influence of the change of the “width of the recessed area”.

[0268] This group of examples is carried out with reference to Example 1, except that the width of the concave region is changed, as follows:

[0269] Example 12a: The width of the recessed area is 20 mm;

[0270] Example 12a: The width of the recessed area is 30 mm.

[0271] Example 13

[0272] The method is carried out in accordance with Example 1, except that the depth of the hole is 35.7 μm, the diameter of the hole is 184.3 μm, the spacing between the holes is 450 μm, and the holes are randomly distributed.

[0273] Embodiment 14

[0274] The method is carried out with reference to Example 2, except that the depth of the groove is 42.9 μm, the width of the groove is 459.5 μm, the spacing between the grooves is 520 μm, and the grooves are randomly distributed.

[0275] Example 15 Group

[0276] This group of examples is used to illustrate the impact of changes in the "weight content of the M element in the lithium cobalt oxide material".

[0277] This group of examples is carried out with reference to Example 1, except that the weight content of the M element in the lithium cobalt oxide material is changed, as follows:

[0278] Example 15a: The weight content of the M element in the lithium cobalt oxide material is 5000 ppm;

[0279] Example 15b: The weight content of the M element in the lithium cobalt oxide material is 18000 ppm.

[0280] Comparative Example 1

[0281] The process is carried out in accordance with Example 1, except that the thickness h2 of the second positive electrode active layer is 200 μm, and h1+h2*D2 / D1=458.3.

[0282] Comparative Example 2

[0283] The process is carried out in accordance with Example 1, except that the thickness h1 of the first positive electrode active layer is 250 μm, and h1+h2*D2 / D1=423.3.

[0284] Comparative Example 3

[0285] The method is carried out in accordance with Example 1, except that the average particle size D1 of the ternary material is 45 μm and the specific surface area is 0.55 m 2 / g, the average particle size D2 of lithium cobalt oxide is 7μm, and the specific surface area is 0.33m 2 / g, corresponding h1+h2*D2 / D1=37.44.

[0286] Comparative Example 4

[0287] The process is carried out in accordance with Example 1, except that the depth h of the concave portion is 93 μm, and h>0.5H-0.01.

[0288] Comparative Example 5

[0289] The process is carried out in accordance with Example 1, except that the ternary material and the lithium cobalt oxide material are mixed and coated in a single layer.

[0290] Comparative Example 6

[0291] The same procedure was followed as in Example 1, except that there was no recessed region in the positive electrode active material layer.

[0292] Test Case

[0293] The lithium ion batteries prepared in the examples and comparative examples were tested as follows:

[0294] (1) Liquid retention coefficient

[0295] According to the production process, a certain amount of electrolyte is injected, and then the battery undergoes formation and sorting, and part of the electrolyte will be consumed. During the second sealing process, the excess electrolyte will be extracted and packaged. Therefore, the liquid retention amount = battery cell mass + electrolyte injection amount - battery cell mass after second sealing. Calculation of liquid retention coefficient: liquid retention coefficient = liquid retention amount / battery capacity.

[0296] (2) Cycle test:

[0297] The thickness of the bending area of ​​the sample tested at 25℃±5℃ is recorded as H1;

[0298] ①25℃ constant temperature room, 0.2C discharge to cut-off voltage 3V; let stand for 10min, charge to 50% SOC at 1C constant current, charge to 100% SOC at 0.7C constant current to upper limit voltage 4.45V, cut-off current 0.05C; let stand for 10min; pause, put the sample at room temperature and let it stand for about 2h, after the sample temperature cools to room temperature, measure the voltage, internal resistance, thickness, DC internal resistance (1C 3s) under the first full charge (100% SOC);

[0299] ②Discharge at 0.5CP to a cut-off voltage of 3.0V; let stand for 10 minutes; charge at 1C constant current to 50% SOC, charge at 0.7C constant current to 100% SOC, charge to an upper limit voltage of 4.45V, and a cut-off current of 0.05C; let stand for 10 minutes; repeat this process 1000 times according to step ②;

[0300] ③ Charge to 50% SOC at 1C constant current, and charge to 100% SOC at 0.7C constant current to an upper limit voltage of 4.45V, with a cut-off current of 0.05C; after 600 cycles, take the sample to room temperature and let it rest for about 2 hours. After the sample temperature cools to room temperature, measure the stage data of the fully charged state, and measure the thickness of the bending zone as H2;

[0301] Measure the thickness of the bending zone in the full power state every 100 times (Note: when measuring process data, the sample needs to be left at room temperature for about 2 hours, and then measured after the sample cools to room temperature).

[0302] The thickness expansion rate of the bending zone = (H2-H1)*100% / H1.

[0303] (3) Furnace temperature test:

[0304] At 25℃±3℃, discharge at 0.2C to a cut-off voltage of 3.0V, and let stand for 5min; charge at 0.5C constant current and constant voltage to an upper limit voltage of 4.45V, with a cut-off current of 0.05C; test the voltage, internal resistance, and thickness of the fully charged state (100%SOC) at 25℃±3℃, and take pictures before the test;

[0305] Put the fully charged battery cell into the test box, and heat the test box at a temperature rise rate of (5±2)℃ / min. When the temperature inside the box reaches 140℃±2℃, keep the constant temperature for 60 minutes. After the test is completed, test the voltage and internal resistance, take pictures after the test, and continuously monitor the surface temperature of the battery. Five battery samples are tested in each embodiment, where fire or explosion indicates "failure", and no fire or explosion indicates "pass". The test results are expressed as "number of passes / 5pass", where "3 / 5pass" means 3 out of 5 tests passed.

[0306] (4) Rate performance

[0307] The rate performance of the battery is determined by charging the battery at a rate of 25°C. The details are as follows:

[0308] Test the sample voltage, internal resistance and thickness at 25±5℃, let stand for 10min; discharge at 0.2C to 3.0V, let stand for 10min; charge at a certain rate (0.2C / 0.3C / 0.4C…), cut-off current 0.05C, let stand for 10min, discharge at 0.5C to 3.0V; let stand for 10min. After repeating the above steps for 30T, disassemble the battery after full charge.

[0309] Observe the anode interface. If the anode electrode is golden and normal, and there is no lithium deposition, the battery supports the corresponding rate performance; if there are gray / brown / white particles covering the interface, the battery is lithium deposited, and the corresponding rate performance is not supported at this time. The maximum rate at which the battery does not deposit lithium is the rate performance of the battery. Among them, the rate performance is good when it is above 1.5. Good rate performance is the standard for batteries to leave the factory.

[0310] The obtained results are recorded in Table 1.

[0311] Table 1

[0312]

[0313]

[0314] As can be seen from Table 1, the battery prepared by the wound battery cell of the present invention passes the furnace temperature test at a higher level than that of the comparative example, the battery cell has no abnormal appearance after 600T cycle, the expansion rate of the bending zone is low, there are no black spots in the bending zone, and the rate performance is high, indicating that by adopting a double-layer coating method and setting a recessed area, while controlling the average particle size of the lithium cobalt oxide material and the ternary material and the relationship between the thickness of each active layer, the cycle performance of the battery is improved, the cycle life of the battery is extended, and the safety performance and rate performance of the battery are improved.

[0315] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A wound battery cell, characterized in that: The wound battery cell includes a positive electrode sheet, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, the positive electrode active material layer includes a first positive electrode active layer and a second positive electrode active layer, the first positive electrode active layer is located on the surface of the positive electrode current collector, the second positive electrode active layer is located on the surface of the first positive electrode active layer, the first positive electrode active layer includes a ternary material, the second positive electrode active layer includes a lithium cobalt oxide material, the positive electrode active material layer includes a concave area, the concave area corresponds to the bending area of ​​the wound battery cell, the concave area includes a concave portion, then the positive electrode sheet satisfies the following relationship at the same time: 0.01H≤h≤0.5H-0.01; H=h1+h2; 40≤h1+h2*D2 / D1≤400; Among them, H is the thickness of the positive electrode active material layer, in μm, h is the depth of the recess, in μm, h1 is the thickness of the first positive electrode active layer, in μm, h2 is the thickness of the second positive electrode active layer, in μm, D1 is the average particle size of the ternary material, in μm, and D2 is the average particle size of the lithium cobalt oxide material, in μm.

2. The wound battery cell according to claim 1, wherein: The CB value of the bending zone of the wound battery cell is 1.05-1.25; And / or, the width of the recessed area is 5 mm-20 mm; and / or, the depth h of the recess is 1 μm-50 μm; and / or, h≤h2; and / or, the recess comprises one or more of a hole and a groove; And / or, the ternary material comprises a chemical formula of Li(Ni x Co y Mn 1-x )O2 particles, where 0.5≤x≤0.95, 0.05≤y≤0.

5.

3. The wound battery cell according to claim 2, wherein: The recessed area comprises at least one hole, the depth of the hole is 1 μm-50 μm, the diameter of the hole is 20 μm-200 μm, the spacing between the holes is 20 μm-5000 μm, and preferably, the holes are distributed in a matrix.

4. The wound battery cell according to claim 2, wherein: The recessed area includes at least one groove, the width of the groove is 1 μm-500 μm, the depth of the groove is 1 μm-50 μm, the spacing of the groove is 20 μm-5000 μm, and preferably, the grooves are distributed in a matrix. And / or, the groove passes through or does not pass through both side edges of the positive electrode sheet in the width direction.

5. The wound battery cell according to any one of claims 1 to 4, wherein: 3μm≤h1≤200μm, preferably 20μm≤h1≤100μm; and / or, 20 μm ≤ h2 ≤ 200 μm, preferably 50 μm ≤ h2 ≤ 100 μm; and / or, 0<H≤300μm, preferably 100μm≤H≤200μm; and / or, 3 μm ≤ D1 ≤ 15 μm; And / or, 8μm≤D2≤25μm.

6. The wound battery cell according to claim 5, wherein: The specific surface area of ​​the ternary material is greater than the specific surface area of ​​the lithium cobalt oxide material; And / or, the specific surface area of ​​the ternary material is 0.3m 2 / g-1m 2 / g; And / or, the specific surface area of ​​the lithium cobalt oxide material is 0.07m 2 / g-0.32m 2 / g; And / or, the crystal structure of the lithium cobalt oxide material includes single crystal; And / or, based on the total weight of the first positive electrode active layer, the weight content of the ternary material is 95%-99%; And / or, based on the total weight of the second positive electrode active layer, the weight content of the lithium cobalt oxide material is 94%-99%; And / or, at any two positions in the positive electrode active material layer, the difference in weight content of the ternary material in the positive electrode active material layer per unit area is less than 0.6%, and the difference in weight content of the lithium cobalt oxide material in the positive electrode active material layer per unit area is less than 0.6%.

7. A battery, characterized in that: The battery comprises the wound battery cell according to any one of claims 1 to 6.

8. The battery according to claim 7, wherein The battery has a liquid retention coefficient of 1.8-2.2; And / or, the battery further comprises an electrolyte, the electrolyte comprises an ether nitrile compound, and the weight content y% of the ether nitrile compound is 3%-15% based on the total weight of the electrolyte; Preferably, the ether nitrile compound includes one or more of tetraethylene glycol di(2-cyanoethyl) ether, ethylene glycol di(4-cyanobutyl) ether and ethylene glycol (bis) propionitrile ether.

9. The battery according to claim 8, wherein The battery satisfies the following relationship: 0.03≤y-0.21h≤3.16; And / or, the battery further comprises adhesive paper, the adhesive paper comprises a substrate and an adhesive layer located on one side or both sides of the substrate, and the swelling rate t of the adhesive paper in the electrolyte is t≤15%; And / or, the dissolution rate p of the adhesive tape in the electrolyte is p≤10%.

10. The battery according to claim 9, wherein The substrate comprises one or more of polyethylene terephthalate, polyimide and polyolefin; And / or, the adhesive layer comprises one or more of polyacrylate, rubber, polyurethane and organic silica gel, and the rubber comprises one or more of polyisobutylene, polypropylene, styrene-butadiene rubber, styrene-butadiene-styrene terblock copolymer, and styrene-isoprene-styrene block copolymer; And / or, the thickness of the substrate is 10 μm-15 μm; And / or, the thickness of the adhesive layer is 1 μm-8 μm.

Citation Information

Patent Citations

  • Lithium ion secondary battery

    CN111033857A

  • Positive plate and lithium ion battery containing positive plate

    CN112310344A

  • Positive plate and lithium ion battery

    CN112751002A

  • Winding type electrode assembly, battery monomer, battery and electric equipment

    CN116417687A

  • Secondary battery and electric equipment

    CN117012896A